2013
DOI: 10.1183/09031936.00148713
|View full text |Cite
|
Sign up to set email alerts
|

Asthma affects time to pregnancy and fertility: a register-based twin study

Abstract: Coexistence of infertility and asthma has been observed clinically. Therefore, we investigated the association between asthma and delayed pregnancy in a nationwide population-based cohort of twins.A cohort of 15 250 twins living in Denmark (aged 12-41 years) participated in a questionnaire study including questions about the presence of asthma and fertility. Differences in time to pregnancy and pregnancy outcome were analysed in subjects with asthma, allergy and in healthy individuals using multiple regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 40 publications
4
65
1
Order By: Relevance
“…This supports previous findings by TATA et al [14] and GADE et al [10] that showed women with asthma have lower fertility rates when older compared with similarly aged women without asthma. These findings could indicate that the severity, the disease progression and the years exposed to low-grade systemic inflammation, have an influence on fertility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This supports previous findings by TATA et al [14] and GADE et al [10] that showed women with asthma have lower fertility rates when older compared with similarly aged women without asthma. These findings could indicate that the severity, the disease progression and the years exposed to low-grade systemic inflammation, have an influence on fertility.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a registry-based questionnaire study of twins demonstrated that asthma was associated with prolonged time to pregnancy (TTP) and thereby possibly impairs fertility [10]. Additionally, in a more recent study we showed that vascular endothelial growth factor (VEGF) is significantly decreased in the endometrial cavity in women with unexplained infertility and concomitant asthma compared to women without asthma [11].…”
Section: Introductionmentioning
confidence: 87%
“…One problem is that we were unable to include those without children in this survey. However, asthma has been related to delayed time to pregnancy, but not to childlessness [31]. In the current study, the reported numbers of children were not different between asthmatic and nonasthmatic parents (data not shown).…”
Section: Discussionsupporting
confidence: 52%
“…In 2014 more than 200 original articles were published in the ERJ: we were proud to release exciting novel information covering the whole spectrum of respiratory medicine, including epidemiology [18], COPD [19][20][21], asthma [22,23], paediatric pulmonology and cystic fibrosis [24,25], tuberculosis and respiratory infections [26,27], sleep medicine [28], pulmonary vascular medicine [29,30], interstitial lung diseases [31], lung function [32] and lung cancer [33].…”
Section: And Some Star Performancesmentioning
confidence: 99%